MicroRNAs and Drug-induced Kidney Injury - Pavkovic, Mira (Pharmacol Ther, 2016)
Drug-induced kidney injury (DIKI) is a severe complication in hospitalized patients associated with higher probabilities of developing progressive chronic kidney disease or end-stage renal diseases. Furthermore, DIKI is a problem during preclinical and clinical phases of drug development leading to high rates of project terminations. Understanding the molecular perturbations caused by DIKI would pave the way for a new class of therapeutics to mitigate the damage. Yet, another approach to ameliorate DIKI is identifying sensitive and specific translational biomarkers that outperform the current diagnostic analytes like serum creatinine and facilitate early diagnosis. MicroRNAs (miRNAs), a class of non-coding RNAs, are increasingly being recognized to have a two-pronged approach towards DIKI management: 1) miRNAs have a regulatory role in gene expression and signaling pathways thereby making them novel interventional targets and 2) miRNAs enable diagnosis and prognosis of DIKI because of their stable presence in biofluids. In this review, apart from summarizing the literature on miRNAs in DIKI, we report small RNA sequencing results showing miRNA expression profiles at baseline in normal kidney samples from mice and humans. Additionally, we also compared the miRNA expression in biopsies of normal human kidneys to patients with acute tubular necrosis, and found 76 miRNAs significantly downregulated and 47 miRNAs upregulated (FDR adjusted p<0.05, +/−2-fold change). In summary, we highlight the transformative potential of miRNAs in therapeutics and translational medicine with a focus on drug-induced kidney damage.